The Millicent Quibb School of Etiquette for Young Ladies of Mad Science - McKinnon, Kate, 1984- (Millicent Quibb School, 2024)
"Three orphaned siblings become the pupils of the mysterious Professor Millicent Quibb and enter the world of mad science"--